IMPROVING THE ENERGY EFFICIENCY OF ELECTRIC RECEIVERS BY IMPROVING ELECTRICITY QUALITY INDICATORS - Федоров, Михаил; Михайлов, Иван; Галущак, Иван; Курляк, Петр; Михайлов, Николай (SWorldJournal, 2020)
The article analyzes the operation of electric receivers in conditions of deterioration of electricity quality. The quality of electricity and the consequences of its deterioration have a complex impact on the operation of electrical equipment The amount